Predictors of Mortality in HPV‐Associated Oropharynx Carcinoma Treated With Surgery Alone. (1st November 2019) - Han, Mary; Stanford‐Moore, Gaelen B.; Larson, Andrew R.; Schoppy, David W.; Cognetti, David M.; Joshi, Arjun S.; Houlton, Jeffery J.; Ryan, William R.
Abstract : Objective: Survival outcomes for human papillomavirus‐associated oropharynx squamous cell carcinoma (HPV + OPSCC) treated with surgery alone are unclear. To increase understanding, we assessed overall survival (OS) outcomes using the national cancer database (NCDB). Methods: We conducted a retrospective analysis of OS of 736 NCDB HPV + OPSCC patients who underwent surgery alone from 2010 to 2014 using univariate and multivariate analyses and the Kaplan‐Meir method. Results: Multivariable analysis found the following independent risk factors for death: American Joint Commission on Cancer (AJCC) 8th edition pathologic stage(p)N2 versus pN0 disease (hazard ratio [HR], 5.5; P = 0.000006), macroscopic extranodal extension (ENE) versus non‐ENE (HR, 4.9; P < 0.02), a positive lymph nodes (LN) percentage of ≥10% (HR, 4.2; P = 0.0002), and five or more positive LNs (HR, 4.9; P = 0.00004). Three‐year OS was significantly worse for AJCC 8th edition pN2 versus pN0 but not for 7th edition pN2 versus pN0 disease. Five‐year OS was significantly worse for positive versus negative surgical margins, AJCC 8th edition stage II versus I, and either microscopic or macroscopic ENE versus non‐ENE positive LNs. For 523 (71%) AJCC 8th edition stage I patients and for 283 (38%) patients who were pT1–T2, with negative margins, pN0–N1, with ≤4 pathologic LNs, without ENE, and with >20 LNs removed during neck dissection, the 3‐year OS rates were 93% and 95%, respectively, and the 5‐year OS rates were 91% and 95%, respectively. Conclusion: In the context of the lack of detail and possible inaccuracies found in the NCDB, surgery alone for AJCC 8th edition stage I HPV + OPSCC, particularly pT1–T2, pN0–N1 with ≤4 pathologic LNs, without ENE, and with negative surgical margins has a high OS. Level of Evidence: 4 Laryngoscope, 130:E423–E435, 2020